BRIDGE RE-DESIGN CLASS A COMPOSITE GIRDER (GIRDER BRIDGE CASE STUDY OF COMPOSITE CLASS C+) RANTAU BAKULA BANJAR DISTRICT - Riyan Noor Cahyo; Syahril Taufik (CERUCUK, 2019)
In Rantau Bakula village are its main bridge girder composite construction. Due to the condition of the existing bridge is felt not designed for vehicles with a large payload then re-design bridge girder composite with spans of 25 m and 9 m wide bridge.In this planning will be carried out load analyzes include: self weight, additional dead load (weight of asphalt and rainwater), load lane "D", pedestrian live load, brake force, load the truck "T", the wind load and earthquake load. Loading method refers to the imposition Standards For RSNI Bridge T-02-2005 whereas the method of structural design of composite bridges refers RSNI T-03-2005 Steel Structural Design For Bridge and SNI 03-1729-2002 on Procedures Design Steel Structures.            From the planning to the pavement reinforcement obtained using principal reinforcement D 13-150 mm with shear D 13-90 mm. The main girder profiles used WF 900 x 300 x 16 x 32 and diaphragm WF 400 x 200 x 8 x 13 shear connector used stud with a size of 12 x 190 mm. The connection between girders using screws with a diameter of 20 mm. Abutment has a height of 2.75 m and a length of 10 m. Used caisson foundation amounted to 2 pieces with a length of 2 meters and a diameter of 3.5 m. Keywords: Rantau Bakula, bridge, girders, composite abutments, caisson.